1997
DOI: 10.1523/jneurosci.17-09-03178.1997
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Magnetic Stimulation during Positron Emission Tomography: A New Method for Studying Connectivity of the Human Cerebral Cortex

Abstract: We describe a new technique permitting the mapping of neural connections in the living human brain. The method combines two well established tools of brain research: transcranial magnetic stimulation ( TMS) and positron emission tomography (PET). We use TMS to stimulate directly a selected cortical area while simultaneously measuring changes in brain activity, indexed by cerebral blood flow (CBF), with PET. The exact location of the stimulation site is achieved by means of frameless stereotaxy. In the first st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
338
1
23

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 651 publications
(371 citation statements)
references
References 44 publications
9
338
1
23
Order By: Relevance
“…However, although TMS's penetration is limited to 2 cm, studies combining TMS with functional neuroimaging have revealed effects of TMS that are distant from the site of stimulation. 18,59,60 Furthermore, coils with a deeper power of penetration are being investigated for their potential clinical use. 61 In summary, although no recommendations on the use of this technique can be given, the promising results, non-invasiveness of TMS and good tolerability support further research with this technique.…”
Section: Discussionmentioning
confidence: 99%
“…However, although TMS's penetration is limited to 2 cm, studies combining TMS with functional neuroimaging have revealed effects of TMS that are distant from the site of stimulation. 18,59,60 Furthermore, coils with a deeper power of penetration are being investigated for their potential clinical use. 61 In summary, although no recommendations on the use of this technique can be given, the promising results, non-invasiveness of TMS and good tolerability support further research with this technique.…”
Section: Discussionmentioning
confidence: 99%
“…rTMS procedure. To target the same cortical location in all subjects, we used a procedure developed in our first TMS-PET study (for details, see Paus et al, 1997;Paus, 2002), which takes advantage of both standardized stereotaxic space and frameless stereotaxy. In short, MR images (160 continuous 1-mm thick saggital slices) of the subject's brain were acquired and the MDLFC coordinates in MNI space were transformed to the subject's brain coordinate (ie 'native') space.…”
Section: Experiments 1: the Effect Of 10-hz Rtms On Affect And Speechmentioning
confidence: 99%
“…Initial studies used fluorodeoxyglucose (George et al, 1995;Kimbrell et al, 1999) or oxygen (O15) (Paus et al, 1997;Paus and Wolforth, 1998) positron emission tomography (PET). Our group at the Medical University of South Carolina (MUSC) pioneered and developed a technique for interleaving TMS with blood oxygen level-dependent (BOLD) functional magnetic resonance imaging (fMRI) Shastri et al, 1999).…”
Section: Introductionmentioning
confidence: 99%